P. gingivalis in Periodontal Disease and Atherosclerosis – Scenes of Action for Antimicrobial Peptides and Complement - Hussain, Mehak; Stover, Cordula M.; Dupont, Aline (Frontiers in Immunology, 2015)
According to the NHS, it is estimated that over 50% of the adult population are, to some extent, affected by gum disease and approximately 15% of the UK population have been diagnosed with severe periodontitis. Periodontitis, a chronic polymicrobial disease of the gums, causes inflammation in its milder form, whereas in its severe form affects the surrounding tissues and can result in tooth loss. During periodontitis, plaque accumulates and sits between the junctional epithelium and the tooth itself resulting in inflammation and the formation of a periodontal pocket. An interface is formed directly between the subgingival bacteria and the junctional epithelial cells. Bacterial pathogens commonly associated with periodontal disease are, among others, Porphyromonas gingivalis, Tannerella forsythia and Treponema denticola, together known as the “red complex”. This review will mostly concentrate on the role of P. gingivalis, a gram-negative anaerobic bacterium and one of the major and most studied contributors of this disease. Because periodontal disease is associated with the development of atherosclerosis, it is important to understand the local immune response to P. gingivalis. Innate immune players, in particular complement and antimicrobial peptides and their effects with regard to P. gingivalis during periodontitis and in the development of atherosclerosis, will be presented.